2012
DOI: 10.1021/jz201559g
|View full text |Cite
|
Sign up to set email alerts
|

Templating Highly Crystalline Organic Semiconductors Using Atomic Membranes of Graphene at the Anode/Organic Interface

Abstract: Charge and energy transport in organic semiconductors is highly anisotropic and dependent on crystalline ordering. Here, we demonstrate a novel approach for ordering crystalline organic semiconductors, with orientations optimized for optoelectronics applications, by using a single monolayer of graphene as a molecular template. We show, in particular, that large-area graphene can be integrated on metals and oxides to modify their surface energies and used to template copper phthalocyanine (CuPc), a prototypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…[27][28][29][30] From these studies, one seemly can draw the same conclusion that the planar molecules prefer to be stacked with face-on geometry on graphene substrates, namely, the planar aromatic ring is parallel to the graphene sheets, due to the favorable p-p type MS interaction. They also observed that the molecules prefer to nucleate at grain boundaries or wrinkle positions of the graphene substrates and then gradually grow into larger islands as the film thickness increases.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…[27][28][29][30] From these studies, one seemly can draw the same conclusion that the planar molecules prefer to be stacked with face-on geometry on graphene substrates, namely, the planar aromatic ring is parallel to the graphene sheets, due to the favorable p-p type MS interaction. They also observed that the molecules prefer to nucleate at grain boundaries or wrinkle positions of the graphene substrates and then gradually grow into larger islands as the film thickness increases.…”
mentioning
confidence: 76%
“…38 This observation is also in good consistent with studies on CuPc film growing on other graphene substrates such as transferred graphene substrates. 29,30 On the RG substrate, however, the morphology of CuPc film differs considerably from that on the SG substrate. Shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of applications for graphene has been proposed following the isolation of individual monolayer sheets by Geim in 2005 [1]. These applications include the use of graphene as a transparent electrode material for organic light emitting diodes or organic photovoltaics [2][3][4][5], as a growth modifier for organic crystals [6][7][8], in single molecule sensors [9][10][11], or as a replacement of silicon in future high performance electronics [12]. All of these applications require some means of functionalization of the pristine graphene sheets, either simply for electronic contacting or to alter its properties as needed, e.g., to induce a band gap for the use in a field effect transistor.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several methods for improving the crystallinity of organic thin films have been proposed, such as thermal heating of the substrate during deposition, thermal-or solvent-annealing after thin-film fabrication, and surface treatment of the substrate. [1][2][3][4][6][7][8][9] However, applying external fields during the thin-film fabrication process might make it possible to control both the orientation and crystallinity of thin films with ease over large areas without a time-consuming and complicated fabrication process. [10][11][12][13] In particular, the use of a magnetic field is a powerful technique for controlling the orientation of various kinds of materials such as carbon nanotubes 14,15 and liquid crystalline (LC) mesogens.…”
mentioning
confidence: 99%